STRATEGI KETERSEDIAAN INFRASTRUKTUR PERMUKIMAN DI DISTRIK TAMI, KOTA JAYAPURA - Matulessy, Beni D. J.; Rusim, Dewi Ana; Manalu, Janviter (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
Due to the functioning of the Youtefa Bridge has had an impact on regional development in the Muara Tami District. This area was once a transmigration area which was transformed into a residential and trade area. This research aims to identify and analyze the current growth of settlements in the Muara Tami District, the availability of residential infrastructure and develop strategies for improving existing infrastructure. Data collection was carried out by observation and interviews, then analyzed qualitatively. The research results show that Residential growth in Muara Tami District area is currently very rapid, marked by the growth of new housing, commercial buildings and many land conversions occurring, namely from agricultural land to land for settlement in the form of housing and plots of land. The growth of settlements in Muara Tami District area has not been fully supported by the availability of adequate residential infrastructure.Public infrastructure is basically provided by the government, including roads, drainage, electricity and on-site Waste water treatment plant systems. However, everything is not in the best condition according to standards because it has not been upgraded and there is a lack of maintenance. Clean water and drinking water infrastructure is basically not yet available, so people still rely on drilled wells, dug wells, bottled water and refillable clean water supplies. There is no green open space specifically in the form of a playground (play ground). It is necessary to develop strategies for improving and maintaining existing but not yet optimal infrastructure, including road infrastructure, sanitation and drainage, waste management and housing. Meanwhile, efforts must be made to develop infrastructure that does not yet exist, such as green open space (play ground) and clean water/drinking water.